Sosyal Bilgiler Dersi 7. Sınıf Öğretim Programı “Yaşayan Demokrasi” Ünitesinin Kazanımlarına Ulaşma Derecesinin Öğretmen Göru?şlerine Göre Değerlendirilmesi - Ezer, Feyzullah; Çelik, Sami (Harran Üniversitesi, 2016)
Bu araştırmanın amacı, 7. Sınıf Sosyal Bilgiler Dersi “Yaşayan Demokrasi” Ünitesinin Kazanımlarına ulaşma derecesinin öğretmen göru?şlerine göre değerlendirilmesidir. Bu değerlendirmenin yapılmasında cinsiyet, mesleki kıdem, mezun olunan lisans programı, öğrenim durumu gibi değişkenler esas alınmıştır. Betimsel nitelik arz eden nicel araştırma yöntemlerinden birisi olan betimleyici yöntemlerden, “alan taraması (survey)” yöntemi kullanılmıştır. Araştırma örneklemini, evreni temsil niteliğine sahip olan Elazığ İl Merkezinde bulunan 2014-2015 Eğitim Öğretim Yılında görev yapan ve ölçeği cevaplamayı kabul eden 106 Sosyal Bilgiler Öğretmeninden oluşturulmuştur. Verilerin elde edilmesinde, Koçyiğit (2002) tarafından geliştirilmiş ölçekten yararlanılmıştır. Bu çalışmada, anlamlılık du?zeyi p=0.05 du?zeyi kabul edilmiştir. Araştırmaya katılan Sosyal Bilgiler Öğretmenlerine göre öğrenciler, öğretim su?recinde u?nitede yer alan beş kazanıma ulaşmışlardır. Ancak demokrasinin yaşaması adına bu kazanımların yeterli olmadıkları sonucuna da varılmıştır.

The aim of the research was to evaluate the extent of reaching the objectives of the unit "alive democracy" in the 7th grade social science curriculum based on teachers’ opinions. While evaluating, some variations such as gender, profession experience, graduation program and educational background were taken into consideration. To obtain the data, a survey was utilised. The sample of the research was 106 social science teachers who were working in Elazığ province in Turkey during the 2014-2015 academic term. To analyze the data, arithmetic mean, standard deviation calculations, for homogenous deviation, t-test and variance analysis, for nonhomogenous deviation MWU and KWH tests were used. According to the participant teachers, students obtained the objectives of the "Alive Democracy" unit in 7th Grade social science course curriculum at desired levels. Moreover, teachers adopted the objectives of the "Alive Democracy" unit in 7th Grade social science course curriculum and they thought that its application was successful. While there was no difference among teachers’ opinions in terms of their gender, there was a meaningful difference in relation to working experience. Young teachers (1-5 Year) adopted the objectives better than 16 Year and over experienced teachers did. The difference among teachers' opinions related to their graduation level was in favor for master degree social science education.
Evaluating the Extent of Reaching the Objectives of the Unit "Alive Democracy" in 7th Grade Social Science Curriculum Based on Teachers’ Opinion